THE IMPACT OF FACILITY AVAILABILITY ON TOURISTS’ REVISIT INTENTION: THE MEDIATING ROLE OF PERCEIVED RISK IN COASTAL TOURISM - Anggraini, Fitria Nela; Susan, Ling Ling Widya; Warsitasari, Wahyu Dwi; Yudiantoro, Deny (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
A tourist attraction's viability is influenced by both its popularity and the number of return visitors.  Unsatisfactory visitor experiences, especially with regard to perceived risk and facility availability, are believed to have contributed to the drop in visitation.  The low intention of tourists to return is a result of both causes.  The link between these factors is explained theoretically by the Theory of Planned Behavior.  This study uses the Theory of Planned Behavior method to examine how risk perception and facility availability affect visitors' intentions to return to beach tourist destinations. This study employs a quantitative, associative research methodology.  The major data sources for this quantitative data type are surveys completed by 120 respondents.  The study's population consists of visitors to Tulungagung's Gemah Beach.  Non-probability sampling of the accidental sampling kind is the method employed.  Structural Equation Modelling (SEM)-PLS was used to map the connections between variables in the data. This study found that (1) the availability of facilities significantly affects risk perception, (2) the availability of facilities significantly affects revisit intention, (3) risk perception affects revisit intention through, and (4) risk perception mediates the effect of facility availability on revisit intention. Based on these findings, it is recommended to improve the availability and quality of facilities to reduce risk perception, thereby effectively encouraging revisit intentions.